Biofilm Formation of Helicobacter pylori in Both Static and Microfluidic Conditions Is Associated With Resistance to Clarithromycin - Paweł Krzyżek; Paweł Migdał; Rossella Grande; Grażyna Gościniak (Frontiers in Cellular and Infection Microbiology, 2022)
It is widely accepted that production of biofilm is a protective mechanism against various type of stressors, including exposure to antibiotics. However, the impact of this structure on the spread of antibiotic resistance in Helicobacter pylori is still poorly understood. Therefore, the aim of the current research was to determine the relationship between biofilm formation and antibiotic resistance of H. pylori. The study was carried out on 24 clinical strains with different resistance profiles (antibiotic-sensitive, mono-resistant, double-resistant and multidrug-resistant) against clarithromycin (CLR), metronidazole (MTZ) and levofloxacin (LEV). Using static conditions and a crystal violet staining method, a strong correlation was observed between biofilm formation and resistance to CLR but not MTZ or LEV. Based on the obtained results, three the strongest and three the weakest biofilm producers were selected and directed for a set of microfluidic experiments performed in the Bioflux system combined with fluorescence microscopy. Under continuous flow conditions, it was observed that strong biofilm producers formed twice as much of biofilm and created significantly more eDNA and in particular proteins within the biofilm matrix when compared to weak biofilm producers. Additionally, it was noticed that strong biofilm producers had higher tendency for autoaggregation and presented morphostructural differences (a greater cellular packing, shorter cells and a higher amount of both OMVs and flagella) in relation to weak biofilm counterparts. In conclusion, resistance to CLR in clinical H. pylori strains was associated with a broad array of phenotypical features translating to the ability of strong biofilm formation.